Implementing a Love-Based Curriculum to Prevent Adolescent Radicalization in Islamic Religious Education - Dina Indriana; Rijal Firdaus; Siti Ngaisah; Imroatun; Zainab Binti Muhamad Ahmad (Women, Education, and Social Welfare, 2026)
This study examines the implementation of the Love-Based Curriculum (Kurikulum Berbasis Cinta/KBC) as a preventive educational framework for adolescent radicalization within Islamic Religious Education. A qualitative descriptive field design was applied in selected Madrasah Aliyah in Banten Province. Participants comprised school principals, vice principals for curriculum affairs, Islamic Religious Education teachers, and students selected purposively on the basis of their involvement in curriculum planning, classroom implementation, and character-building activities. Data were obtained through interviews, classroom observations, document review, and contextual analysis of relevant policy and scholarly literature. The material was analyzed descriptively through data reduction, data display, content interpretation, and conclusion drawing. The analysis identified four interrelated implementation domains: a humanistic-religious pedagogical orientation, integration of love-based values across Islamic Religious Education subjects, consistent habituation through school routines, and the strengthening of religious moderation within a safe and respectful school climate. These domains may support empathy, constructive belonging, dialogical learning, respect for difference, and resistance to hate-based narratives. The findings do not establish a causal reduction in radical attitudes; rather, they position KBC as a contextually relevant whole-school framework whose preventive potential depends on teacher modeling, institutional consistency, family engagement, and critical religious and digital literacy. Further multi-site and outcome-oriented research is needed to assess its longer-term effects.